Perbedaan Sinonim Kata Manusia Dalam Al-Qur’an - Fakron Jamalin (Institut Agama Islam Darusssalam Blokagung, 2021)
Arabic is a language that is rich in synonyms. The words that will be studied in this scientific article are words that have human meaning. In the Qur'an there are more than two words used to refer to humans, namely: basyar, insan, annas, bani adam. The four words are translated into Indonesian by humans. This single translation cannot reflect the complete meaning of each because the synonyms are not completely similar. Therefore, this study was made to answer the differences that exist in the four words. The method used is the method of collecting the corpus from the Qur'an and followed by the comparison technique of equating and distinguishing then analyzed by means of component analysis. From the analysis carried out, the four words have differences in terms of components of meaning consisting of social, character, and worship aspects.